2021
DOI: 10.1007/s40670-021-01248-4
|View full text |Cite
|
Sign up to set email alerts
|

Post-Clerkship Curricular Reform: Specialty-Specific Tracks and Entrustable Professional Activities to Guide the Transition to Residency

Abstract: The development of core entrustable professional activities (EPA) for entering residency and Accreditation Council for Graduate Medical Education’s milestones have spurred thinking about the fourth year of medical school as a transition to residency. In this monograph, we lay out our specialty focused post-clerkship curriculum and report learner and residency director perceptions over the first three years of implementation. Ongoing curricular monitoring has reinforced core principles but has also informed act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 24 publications
2
4
0
Order By: Relevance
“…[7][8][9] Recurrent areas of struggle include teamwork and acculturating to an interprofessional team environment, communication, self-directed and self-regulated learning, organization and time management, preventing medical errors and promoting safety, and medical knowledge. [7][8][9][10][11][12][13][14] Student-reported challenges are further corroborated by similar data from medical school faculty and residency program directors. 10,[13][14][15][16][17][18] What if UME programs looked beyond traditional mechanisms of teaching these competencies and integrated them earlier in the curriculum to gradually build students' skills in these areas?…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…[7][8][9] Recurrent areas of struggle include teamwork and acculturating to an interprofessional team environment, communication, self-directed and self-regulated learning, organization and time management, preventing medical errors and promoting safety, and medical knowledge. [7][8][9][10][11][12][13][14] Student-reported challenges are further corroborated by similar data from medical school faculty and residency program directors. 10,[13][14][15][16][17][18] What if UME programs looked beyond traditional mechanisms of teaching these competencies and integrated them earlier in the curriculum to gradually build students' skills in these areas?…”
Section: Introductionsupporting
confidence: 59%
“…[7][8][9][10][11][12][13][14] Student-reported challenges are further corroborated by similar data from medical school faculty and residency program directors. 10,[13][14][15][16][17][18] What if UME programs looked beyond traditional mechanisms of teaching these competencies and integrated them earlier in the curriculum to gradually build students' skills in these areas? Many medical school curricula currently include required or voluntary research projects, offer scholarly concentration programs, and/or integrate research training across the curriculum.…”
Section: Introductionsupporting
confidence: 59%
“…First, students have generally found learning with peers entering the same field to be valuable. 26 , 27 Specifically, one qualitative study demonstrated that graduates from TTR courses value the ability to reflect and evolve their professional identity as a resident in a specialty with a unique culture. 28 Second, allowing specialty differentiation may permit higher retention of information by decreasing the cognitive load involved in transferring learning from one specialty context to another.…”
Section: Recommendations For Transition To Residency Course Implement...mentioning
confidence: 99%
“…[3][4][5][6][7] The progression from undergraduate medical education to graduate medical education has been the subject of several research studies. [8][9][10][11][12][13] In contrast, transitions during residency have been less well investigated, [3][4][5]7,14 particularly in-depth explorations of trainee perspectives and emotions during this transition.…”
Section: Introductionmentioning
confidence: 99%
“…These new roles are often assumed with little more than brief resident‐as‐teacher and leadership workshops and retreats 3–7 . The progression from undergraduate medical education to graduate medical education has been the subject of several research studies 8–13 . In contrast, transitions during residency have been less well investigated, 3–5,7,14 particularly in‐depth explorations of trainee perspectives and emotions during this transition.…”
Section: Introductionmentioning
confidence: 99%